Teaching and learning in the millennial age. - Markowitz, Richard I.; Reid, Janet R. (Pediatric Radiology, 2018)
Medical education has changed and evolved over the years and has been greatly influenced by advances in technology. While the learners have also changed and the information and skills to be learned and acquired have exponentially increased, the ultimate purpose of medical education has not changed. Our focus is and has always been to improve patient care. This minisymposium highlights selected specific topics that have the potential to enhance our ability to teach and pass along essential ideas and concepts to modern learners, thus improving the health and wellbeing of patients now and in the future.